Autophagy protects against high uric acid-induced hepatic insulin resistance. (1st May 2022) - He, Furong; Wang, Mei; Zhao, Hairong; Xie, De; Lv, Jiaming; Liu, Weidong; Yu, Wei; Wang, Qiang; Chen, Binyang; Xu, Chenxi; Yamamoto, Tetsuya; Koyama, Hidenori; et al.
Abstract: Uric acid (UA), the end-product of purine metabolism, is closely related to hepatic insulin resistance (IR). Autophagy is a conserved intracellular degradation process maintaining cellular homeostasis. Autophagy plays a protective role in obesity-related hepatic IR, but whether it occurs in high uric acid (HUA)-induced hepatic IR is unclear. In this study, spontaneously elevated UA level induced hepatic IR and facilitated hepatic autophagy degradation in uricase knockout (Uox -/- ) mice. In vitro, HepG2 cells stimulated with HUA medium showed decreased glucose uptake and inhibition of insulin signaling pathways, concomitant with activation of autophagy, as manifested by increased conversion of LC3B–I to –II. Rapamycin, the autophagy activator, alleviated but the autophagy inhibitor trimethyl adenine (3-MA) aggravated HUA-induced IR in HepG2 cells. Similarly, rapamycin ameliorated and 3-MA worsened HUA-induced blood glucose level and hepatic IR in Uox -/- mice. Mechanistically, HUA enhanced AMPKα phosphorylation (p-AMPKα) and inhibited mammalian target of rapamycin phosphorylation (p-mTOR) in HepG2 cells. The levels of p-AMPKα and LC3B-II/I were downregulated in HepG2 cells transfected with small interfering RNA (siRNA) against AMPKα, which suggests that the AMPKα–mTOR pathway was involved in HUA-induced autophagy. Antioxidant N-acetyl-L-cysteine reversed elevated reactive oxygen species levels induced by HUA in HepG2 cells, and AMPKα level was also inhibited, which suggests that AMPKα activation may be derived from reactive oxygen species. Collectively, these findings demonstrate that HUA increased hepatic autophagy, and autophagy activation plays a protective role in hepatic IR, which may suggest a potential therapeutic target for hepatic IR derived from HUA. Highlights: Uricase knockout (Uox−/−) mice developed impaired glucose tolerance and hepatic insulin resistance. High uric acid activates hepatocyte autophagy in vivo and in vitro . Autophagy activation protects against hepatocyte insulin resistance derived from high uric acid.